Disclosure Coaching: An Ask-Tell-Ask Model to Support Clinicians in Disclosure Conversations. Issue 8 (17th December 2021) - Shapiro, Jo; Robins, Lynne; Galowitz, Pamela; Gallagher, Thomas H.; Bell, Sigall
Abstract: Error disclosure is a high-stakes, emotionally charged interaction for patients and families as well as clinicians. A failed disclosure can result in emotional distress, reduced patient and family trust, litigation, and lost opportunities to learn from and prevent subsequent errors. However, many clinicians have little expertise in handling these challenging interactions and can inadvertently make a bad situation worse. Even those clinicians who have had formal disclosure training may have trouble remembering what they were taught when faced with the need to actually discuss an error with patients. Providing just-in-time coaching to clinicians is recommended by national standards. However, there is scant training material to guide error disclosure coaches. Therefore, we developed an "Ask-Tell-Ask" model and materials to guide the disclosure coaching process. The Ask-Tell-Ask model is well-suited to provide clinicians with targeted interactive teaching immediately before a disclosure without overwhelming them with lecture-style facts that they are unlikely to retain. Such teaching would ideally be provided by trained disclosure coaches, available for just-in-time support of clinicians throughout the disclosure process. The Ask-Tell-Ask model can also help risk managers, department heads, clinical managers, attending physicians, service chiefs, and others who assist clinicians with error disclosure. Here, we describe a comprehensive approach to coaching developed over years of coaching experience that incorporates the model, its rationale, step-by-step coaching strategies and guidance (including sample scripts), and organizational considerations regarding implementation of a coaching program to support patient-centered transparent communication after harmful events.